Modified Finite-Difference Time-Domain Method for Hertzian Dipole Source under Low-Frequency Band - Minhyuk Kim (MDPI AG, 2021)
In this paper, a modified finite-difference time-domain (FDTD) method is proposed for the rapid analysis of a Hertzian dipole source in the low-frequency band. The FDTD technique is one of the most widely used methods for interpreting high-resolution problems such as those associated with the human body. However, this method has been difficult to use in the low-frequency band as the required number of iterations has increased significantly in such cases. To avoid this problem, FDTD techniques using quasi-static assumptions in low-frequency bands were used. However, this method was applied only to plane wave excitation, making it difficult to apply to near-field problems. Therefore, a modified approach is proposed, involving the application of the FDTD technique with a quasi-static approximation to an electric and magnetic dipole problem. The results when using the proposed method are in good agreement with those from a theoretical solution. An example of comparison with the standard FDTD method is shown for illustrating the proposed method’s performance.